Coaching-Supported OER Implementation for Learner Self-Regulation in Secondary Blended Learning: A Mixed-Methods Framework - Fatima Al-Rashidi Fatima Al-Rashidi (Educational Innovation and Learning Transformation, 2025)
Open educational resources have been widely promoted as equity-oriented tools for expanding curriculum access in secondary education, yet their integration into blended learning environments consistently underdelivers measurable improvements in learner self-regulation when implementation lacks the pedagogical scaffolding and professional support structures that effective use requires. This paper proposes a mixed-methods framework for coaching-supported OER implementation in secondary blended learning, grounded in the theoretical intersections of OER-enabled pedagogy, self-regulated learning theory, instructional coaching research, and implementation science. The framework identifies four interdependent implementation conditions: OER quality and instructional alignment, coaching-supported teacher capacity development, self-regulation scaffolding embedded within blended task design, and institutional sustainability conditions encompassing leadership, infrastructure, and professional community. A quasi-experimental study involving 155 secondary school learners across two blended learning cohorts, complemented by qualitative interviews with participating teachers and students, provides the evaluative architecture within which these conditions operate. Three quantitative tables present outcome data on learner self-regulation, academic performance, and engagement alongside published benchmarks drawn from the OER, coaching, and self-regulated learning literatures. The paper argues that OER adoption in secondary blended contexts cannot deliver its equity and learning potential without simultaneous investment in teacher coaching, self-regulatory task scaffolding, and the institutional governance conditions that make sustained open practice both professionally rewarding and organizationally coherent. Implications are offered for secondary school leaders, curriculum designers, librarians, and system-level policy makers seeking to build OER-enabled blended learning environments that are equitable, pedagogically rigorous, and sustainably maintained.